2016
DOI: 10.1080/20426445.2016.1162429
|View full text |Cite
|
Sign up to set email alerts
|

Impact of air-plasma treatment at atmospheric pressure on wood and wood extractives

Abstract: This study addresses the question of whether the extractives or the main components of wood are responsible for the alterations in surface energy after air-plasma treatment. For this purpose, x-ray photoelectron spectroscopy was carried out on untreated, microtomed and air-plasma-modified beech wood surfaces. A dielectric barrier discharge at atmospheric pressure was used for plasma modification. The results indicate that air-plasma treatment affects the O/C-ratio and surface energy characteristics of wood sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The increase in contact angle due to ageing proceeded faster on plasma-treated samples (Fig. 1a), which is in line with previous XPS studies ( Avramidis et al 2016). There was, however, no further increase in the contact angle from day 13 to day 27, even though the contact angle of the plasma-treated surfaces was still lower than the contact angle of the fresh reference surface.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The increase in contact angle due to ageing proceeded faster on plasma-treated samples (Fig. 1a), which is in line with previous XPS studies ( Avramidis et al 2016). There was, however, no further increase in the contact angle from day 13 to day 27, even though the contact angle of the plasma-treated surfaces was still lower than the contact angle of the fresh reference surface.…”
Section: Resultssupporting
confidence: 92%
“…The plasma effect on wood is not permanent, as the treated surface will also age. Contact angle measurements indicated that the rate of inactivation of plasma-treated wood surfaces depends on the plasma process parameters (Riedl et al 2014), and XPS measurements showed that the rate can be higher than the natural inactivation process (Avramidis et al 2016). Thermal modification of wood has the opposite effect: it reduces the wettability of wood with water.…”
Section: Introductionmentioning
confidence: 99%
“…Wood Science and Technology (2018) 52:1495-1510 dielectric barrier discharges are mainly used in the setups as direct volume barrier discharge (Topala and Dumitrascu 2007;Acda et al 2012;Altgen et al 2016;Avramidis et al 2016;Hünnekens et al 2016;Peters et al 2017), coplanar surface barrier discharge (Odrášková et al 2008;Černák et al 2009) and remote plasma (Busnel et al 2010;Riedl et al 2014;Hardy et al 2015;Prégent et al 2015a).…”
mentioning
confidence: 99%
“…The plasma surface activation and functionalization are able ASTESJ ISSN: to ensure that perfect finishing result we all want to see when looking at finish products. The objective of this kind of activation is to increase the SFE and subsequently the wettability, adhesion and wicking for laminating, printing, dyeing, gluing, impregnating and other finishing processes [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of our own former experience in plasma-aided capillary impregnation of wood and wooden materials, [9][10][11][12], an oxidative APPA has been applied on the test samples for 60 sec. This study employs a well-known experimental methodology, already used by us [1,[14][15][16][17].…”
mentioning
confidence: 99%